CellMapper: rapid and accurate inference of gene expression in difficult-to-isolate cell types. Issue 1 (December 2016) - Nelms, Bradlee; Waldron, Levi; Barrera, Luis; Weflen, Andrew; Goettel, Jeremy; Guo, Guoji; Montgomery, Robert; Neutra, Marian; Breault, David; Snapper, Scott; Orkin, Stuart; Bulyk, Martha; et al.
Abstract We present a sensitive approach to predict genes expressed selectively in specific cell types, by searching publicly available expression data for genes with a similar expression profile to known cell-specific markers. Our method, CellMapper, strongly outperforms previous computational algorithms to predict cell type-specific expression, especially for rare and difficult-to-isolate cell types. Furthermore, CellMapper makes accurate predictions for human brain cell types that have never been isolated, and can be rapidly applied to diverse cell types from many tissues. We demonstrate a clinically relevant application to prioritize candidate genes in disease susceptibility loci identified by GWAS.